The role of childhood trauma in the development of psychopathology via neurocognitive pathways - Debariya, (International Journal of Research in Medical Sciences, 2025)
Childhood trauma is a potent risk factor for a wide range of psychopathological outcomes. This review synthesizes evidence on how trauma experienced in childhood (before age 12) impacts neurocognitive development and in turn elevates risk for later psychopathology. A comprehensive literature search was conducted focusing on cognitive, behavioral, and neurobiological effects of early trauma, with special emphasis on Indian research alongside international findings. Childhood trauma is associated with broad cognitive difficulties, including attentional bias toward threat, memory processing impairments (e.g., fragmented or overgeneral memories), executive function deficits, and emotion regulation problems. These trauma-induced neurocognitive alterations often mediate the link between early adversity and diverse psychopathological outcomes such as posttraumatic stress, anxiety, depression, and dissociation. Neurobiologically, trauma-exposed children show dysregulation of stress response systems (e.g., HPA axis) and structural and functional brain changes in regions subserving emotion and cognition (e.g., amygdala, hippocampus, prefrontal cortex). Indian studies mirror global findings, with high prevalence of child trauma and evidence of similar neurocognitive sequelae. Childhood trauma can derail neurocognitive development in ways that confer transdiagnostic psychopathology risk. These findings underscore the need for early identification and intervention for trauma-exposed children, culturally informed research (particularly in India), and dimensional frameworks (e.g., RDoC) to understand trauma-related cognitive profiles. Early interventions targeting cognitive and emotional regulation skills may mitigate the progression from childhood trauma to later mental health disorders.